Assessment of Food Security, Food Independence and Community Welfare in Food Insecure Areas - Febriani, Angelina Shierly (Journal of International Conference Proceedings, 2023)
This study aims to analyze the factors that affect food security and its impact on the welfare and economic growth of Javanese society. This research method is correlation analysis with primary sources in the form of books and secondary sources in the form of articles and internet pages. This research is the result of a long-term correlation analysis as an effort to improve economic stability has an attachment between variables that affect the functions of Food Security, Food Independence, and Welfare which affect each other not enough with just one element standing alone. Food Security has a two tailed Pearson correlation that shows strong and positive results on food self-sufficiency and welfare. Food security, food self-sufficiency and welfare are very complex. The success of the program is also the shared responsibility of all components of the Nation and the Republic of Indonesia.